2017
DOI: 10.1177/1053815117748408
|View full text |Cite|
|
Sign up to set email alerts
|

A Pilot Study of a Culturally Adapted Early Intervention for Young Children With Autism Spectrum Disorders in China

Abstract: The purpose of this study was to pilot test the effects of a culturally adapted early intervention influenced by the Early Start Denver Model (ESDM) on reduction of autism symptoms and severity categorization for young children with autism spectrum disorders in China. Participants were randomly assigned to either the control or intervention groups. The children's age ranged from 24 to 60 months in this study. Children in the control group (n = 20) received eclectic intervention services for a minimum of 2 hr p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
0
18
0
3
Order By: Relevance
“…Only four programs (C. Liu et al, 2015; Xu et al, 2018; Zhou et al, 2018; Zou et al, 2005) met the criteria in using evidence-based intervention models (Figure 3(b)). Most included programs targeted multiple objectives or goals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only four programs (C. Liu et al, 2015; Xu et al, 2018; Zhou et al, 2018; Zou et al, 2005) met the criteria in using evidence-based intervention models (Figure 3(b)). Most included programs targeted multiple objectives or goals.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome assessors were blind to group status in only 3 out of the 16 studies (Shum et al, 2019; V. Wong & Kwan, 2010; Xu et al, 2018). Two studies were rated as “high risk” either because they used only self-report instruments (Ji et al, 2014) or the author was presented as the outcome assessor (P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the efficacy of a lowintensity ESDM, which provided less frequent and shorter sessions, and a shorter duration of the intervention [10][11][12][13]. The length of each session and the duration of ESDM intervention were as follows: three hours per week for 15 months by Devescovi et al [13], five hours per week for two months by Xu et al [11], six hours per week for six months by Colombi et al [12], and eight hours per week for six months by Lin et al [10]. Taken together, our ESDM intervention might be defined as a low-intensity ESDM in terms of density and length.…”
Section: Esdm Intervention In This Studymentioning
confidence: 99%
“…Three previous studies have examined the effects of low-intensity ESDM programs, with one in China (Xu et al, 2018) and two in Italy (Colombi et al, 2018; Devescovi et al, 2016). Each study showed favorable results: children with ASD improved in cognitive functioning, language, adaptive behaviors, or ASD symptom severity.…”
mentioning
confidence: 99%